Beyond the “Wild Tribes”: Understanding Modern Afghanistan and Its Diaspora By Ceri Oeppen and Angela Schlenkhoff, eds. (New York: Columbia University Press, 2010. 223 pages.) (American Journal of Islam and Society, 2013)
We have come to expect nothing but bad news about Afghanistan, nothingbut negative prognoses of that troubled state from policymakers, pundits, andjournalists. Only rarely do we hear what scholars of Afghan studies have tosay. In Beyond the “Wild Tribes”: Understanding Modern Afghanistan andIts Diaspora, the country and its people are presented in a far more complicatedfashion than the usual this-place-is-doomed mantra. Contributions includea review and critique of research methodologies in Afghanistan and thediaspora, the role of gender in community-based justice, models of nationaland local governance, the refugee warrior, and migration. There is much tolike about this book, and even those knowledgeable about the complex problemsplaguing the fledgling state will learn something ...